2016
DOI: 10.21276/ambi.2016.03.sp1.ta01
|View full text |Cite
|
Sign up to set email alerts
|

Information Seeking Behavior in Blind People of Iran : a Survey based on Various Experiences faced by them

Abstract: Access to information and its dissemination for the planning of health and social care is essential. While information is not always available as per the needs of the blind people, thus the public libraries and information centers led for meeting the information needs culture and proper knowledge. The study was based on a Descriptiveanalytic method in which we included 384 blind people of both the sex selected by the multi-clustering method from 10 provinces of Iran. Health information of the subjects was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…As per WHO's estimate, a person goes blind every 5 seconds globally. In Iran, there are about 124,165 blind people and 463,431 people with low vision [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per WHO's estimate, a person goes blind every 5 seconds globally. In Iran, there are about 124,165 blind people and 463,431 people with low vision [2].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the current trends and the lack of effective interventions, it is predicted that the number of visually impaired in the worldwide will increase to double by 2020 [4].Causes of blindness vary from country to country and even within a country [5]. The condition of blindness is also one of the most common sensory disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, auditory memory and retrieval abilities of congenitally blind people are superior to those of sighted people [39]. Survey results of the questionnaire showed that blind people of Iran are more inclined to use audio media rather than other media to access or utilize information [40]. Similar research was conducted by Kolarik et al [41].…”
Section: Auditionmentioning
confidence: 59%
“…Data collection involved the use of a researcher-designed questionnaire developed based on various Persian and English resources (10,(14)(15)(16)(17)(18)(19)(20)(21). The content validity of the questionnaire was confirmed by obtaining input from 10 academic staff members experienced in information needs assessment.…”
Section: Data Collection and Measurementmentioning
confidence: 99%